2018
DOI: 10.1371/journal.pcbi.1006337
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing image analysis for plant phenomics to generate ground truth data for machine learning

Abstract: The accuracy of machine learning tasks critically depends on high quality ground truth data. Therefore, in many cases, producing good ground truth data typically involves trained professionals; however, this can be costly in time, effort, and money. Here we explore the use of crowdsourcing to generate a large number of training data of good quality. We explore an image analysis task involving the segmentation of corn tassels from images taken in a field setting. We investigate the accuracy, speed and other qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…In this context, the concept of “ground truth,” which means checking the results of machine learning for accuracy against the real world, is fundamental for validating AI performance. In a radiology context, this might mean confirming diagnoses suggested by AI by comparison to pathological or surgical diagnoses; ground truth is the data assumed to be true [11]. Machine learning has been likened to training a dog: “reinforcing good behaviour, ignoring bad, and giving her enough practice to work out what to do for herself” [12].…”
Section: Definitionsmentioning
confidence: 99%
“…In this context, the concept of “ground truth,” which means checking the results of machine learning for accuracy against the real world, is fundamental for validating AI performance. In a radiology context, this might mean confirming diagnoses suggested by AI by comparison to pathological or surgical diagnoses; ground truth is the data assumed to be true [11]. Machine learning has been likened to training a dog: “reinforcing good behaviour, ignoring bad, and giving her enough practice to work out what to do for herself” [12].…”
Section: Definitionsmentioning
confidence: 99%
“…However, the power of AI/machine learning is limited by the quality and quantity of ground-truth data. This presents an ongoing opportunity for citizen scientists to provide data that improve the utility of the technology itself, as with citizen science approaches regarding ground-truthing [55].…”
Section: Emerging Opportunities and Challengesmentioning
confidence: 99%
“…Even if the feature is unfamiliar to most people, crowdsourcing may be viable if the task is simple and the feature obvious. In a recent study on best practices for crowdsourcing plant feature annotation, Zhou et al (2018) found that, with minimal instruction, anonymous online workers could accurately identify maize male flowers in images where they were clearly visible. Accurate identification of many plant features requires a certain level of expertise, however.…”
Section: Introductionmentioning
confidence: 99%